Vaccination coverage of visually impaired adults and sociodemographic characteristics - Lorita Marlena Freitag Pagliuca; Kariane Gomes Cezario; Emilianny Maria Nogueira dos Reis Silva; Karine Moreira de Melo; Marcos Venícios de Oliveira Lopes (Rev Rene)
This study is aimed at assessing the vaccination coverage of visually impaired adults and their socio-demographic characteristics. Quantitative, exploratory and descriptive research, involving 41 visually impaired adults in an association of the blind in Fortaleza, CE, between February and May/2011. For data collection semi-structured questionnaire was used with these variables: name, gender, schooling and vaccination status. The socio-demographic characteristics revealed that the visually impaired were mainly male (63.41%); between 20 and 49 years of age (95.92%) and secondary education level (79.92%). Intervals of confidence according to most of the people with such impairment were vaccinated with the double adult and triple viral. It was concluded that they did not receive a Vaccination Card suitable for their reading, so they are partially immunized and they are susceptible to immune preventable diseases. Health and mainly nursing professionals need to take intervention measures, establishing plans of actions focused on the main prevention measures.